2001
DOI: 10.1073/pnas.241320298
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane rafts play a critical role in HIV-1 assembly and release

Abstract: HIV-1 particle production occurs in a series of steps promoted by the viral Gag protein. Although it is well established that assembly and release take place at the plasma membrane, the nature of membrane assembly sites remains poorly understood. We show here that Gag specifically associates with cholesterol-enriched microdomains (''rafts'') at the plasma membrane. Kinetic studies demonstrate that raft association follows membrane binding, and the analysis of Gag mutants reveals that, whereas the N terminus of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
605
1
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 628 publications
(653 citation statements)
references
References 56 publications
39
605
1
8
Order By: Relevance
“…Importantly, since lipid raft formation and protein association with lipid rafts occur in the Golgi complex (14), such a putative glycoprotein and tegument protein concentrating function of lipid rafts may also be significant for efficient alphaherpesvirus budding and particle formation, as has been hypothesized recently (17,23,26). In this context, it is interesting that lipid rafts have recently been shown to serve as budding platforms for several enveloped viruses, such as human immunodeficiency virus, Ebola virus, influenza virus, and measles virus (1,28,35,36,40), and that such lipid raft-mediated budding has been hypothesized to explain pseudotyping of different viruses, including HSV (37). Further, the viral glycoprotein distribution in the HSV virion envelope has been shown to be nonrandom, which has been hypothesized to be caused by association of viral glycoproteins with lipid rafts (17).…”
Section: Vol 78 2004 Lipid Raft Association Of Prv Glycoproteins 5285mentioning
confidence: 97%
“…Importantly, since lipid raft formation and protein association with lipid rafts occur in the Golgi complex (14), such a putative glycoprotein and tegument protein concentrating function of lipid rafts may also be significant for efficient alphaherpesvirus budding and particle formation, as has been hypothesized recently (17,23,26). In this context, it is interesting that lipid rafts have recently been shown to serve as budding platforms for several enveloped viruses, such as human immunodeficiency virus, Ebola virus, influenza virus, and measles virus (1,28,35,36,40), and that such lipid raft-mediated budding has been hypothesized to explain pseudotyping of different viruses, including HSV (37). Further, the viral glycoprotein distribution in the HSV virion envelope has been shown to be nonrandom, which has been hypothesized to be caused by association of viral glycoproteins with lipid rafts (17).…”
Section: Vol 78 2004 Lipid Raft Association Of Prv Glycoproteins 5285mentioning
confidence: 97%
“…Many papers suggested that lipid rafts were involved in various cellular processes such as signal transduction, apoptosis or protein sorting [20,21]. They have also been shown to play a role in HIV or influenza viruses infection processes [22][23][24].…”
Section: Lipid Microdomains and Membrane Raftsmentioning
confidence: 99%
“…A consensus definition of membrane rafts emerged from the Keystone Symposium on Lipid Rafts and Cell Function (March [23][24][25][26][27][28]2006): "Membrane rafts are small (10-200nm), heterogeneous, highly dynamic, sterol-and sphingolipid-enriched domains that compartmentalise cellular processes. Small rafts can sometimes be stabilised to form larger platforms through protein-protein and protein-lipid interactions" [41].…”
Section: Lipid Microdomains and Membrane Raftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsaturated fatty acids block HIV budding [126] Mycobactin mediates iron supply within macrophages [32] FA Affinity of HIV Gag protein is regulated by myristoyl switch [127] Presentation of glycerophospholipids, sulfolipids and mycolates via CD1 receptors [58,132,133] GP Golgi-derived viruses have different phospholipid (incl semilysobisphosphatidic acid) composition depending on the precise site of budding [7,128] HIV-like particle assembly is regulated by inositol phosphates [129] HIV-1 Gag targeting is regulated by PIP2 [130] Vaccinia virus envelope protein p37 has lipase activity [131] Nef transports cholesterol to site of HIV budding [134] ST Budding occurs from glycolipid-enriched membrane lipid rafts [8,[135][136][137] Table summarizing the reported involvement of lipids, both from the host as well as the pathogen, during various stages of host-pathogen interaction ( Fig. 1).…”
Section: Glmentioning
confidence: 99%